Modulating protein-protein interaction networks in protein homeostasis. - Zhong, M.; Lee, G. M.; Sijbesma, E.; Ottmann, C.; Arkin, M. R
Protein-protein interactions (PPIs)occur in complex networks. These networks are highly dependent on cellular context and can be extensively altered in disease states such as cancer and viral infection. In recent years, there has been significant progress in developing inhibitors that target individual PPIs either orthosterically (at the interface)or allosterically. These molecules can now be used as tools to dissect PPI networks. Here, we review recent examples that highlight the use of small molecules and engineered proteins to probe PPIs within the complex networks that regulate protein homeostasis. Researchers have discovered multiple mechanisms to modulate PPIs involved in host/viral interactions, deubiquitinases, the ATPase p97/VCP, and HSP70 chaperones. However, few studies have evaluated the effect of such modulators on the target's network or have compared the biological implications of different modulation strategies. Such studies will have an important impact on next generation therapeutics.
Keywords: PROTEIN-PROTEIN INTERACTIONS; PROTEIN HOMEOSTASIS